The effect of job stress, job satisfaction on the life satisfaction of knowledge workers in China - Xiao, Yunzhu (2022)
This study examined the relationship between job stress, job satisfaction, and life satisfaction among knowledge workers in China. The study identified the theoretical basis and methodology through reviewing the previous literature. The final questionnaire was appropriately modified from a well-established scale, and the sample consisted of 167 knowledge workers from across China. The study’s final results were derived through linear regression analysis, which revealed that perceived job stress could predict job satisfaction and life satisfaction in a negative way among knowledge workers in China. I further validated that knowledge workers' job satisfaction partially mediates the relationship between job stress and life satisfaction, which meant that the job stress of knowledge workers could directly affect life satisfaction and also affect life satisfaction through job satisfaction. The results of this study can be helpful to company administrators and can help them to improve their knowledge workers' job satisfaction by reducing their job stress, which ultimately acts positively on life satisfaction. From an academic perspective, the current study constitutes the first to address the relationship between job stress and life satisfaction for knowledge workers, and also fills a research gap by validating the role of job satisfaction as a mediator.